A novel CaO nanocomposite cross linked graphene oxide for Cr(VI) removal and sensing from wastewater. (August 2022) - Singh, Simranjeet; Naik, T.S. Sunil Kumar; Anil, Amith G.; Khasnabis, Sutripto; Nath, Bidisha; U, Basavaraju; Kumar, Vineet; Garg, V.K.; Subramanian, S.; Singh, Joginder; Ramamurthy, Praveen C.
Abstract: A novel green nanocomposite has been prepared by immobilizing CaO nanoparticles (CaO NPs) on the surface of graphene oxide. Biogenic CaO-NPs were synthesized from Lala clamshells. Morphological and structural characterizations of the nanocomposite were studied extensively. The adsorption capacity (qmax ) of the nanocomposite for removing Cr(VI) was 38.04 mg g −1 . In addition to this, the adsorption data were adequately simulated with Langmuir, Freundlich, Temkin, and pseudo-second-order models, suggesting that the adsorption process was the combination of external mass transfer and chemisorption. Electrostatic interaction was the dominant mechanism for Cr(VI) removal. In addition, the synthesized nanocomposites also serve as an excellent sensor for Cr(VI) sensing, with a limit of detection (LOD) of 0.02 μM utilizing electrochemical methods. Therefore, this green nanocomposite can simultaneously serve as an adsorbent and sensor for Cr(VI)removal from aqueous solutions. Graphical abstract: Image 1 Highlights: Clam Sea shell waste was used for production of nanocomposites using CaO and GO. Nanocomposite showed maximum adsorption capacity of 38.04 mg/g. Chemisorption mechanisms accounted for Cr (VI) removal using CaO-GO. The developed sensor exhibited catalytic behavior towards the Cr(VI) sensing in terms of selectivity and sensitivity. Real-world sample analysis was carried out using tap water samples.